Utilization of fly ash with silica fume and properties of Portland cement-fly ash-silica fume concrete - Nochaiya,T. (Elsevier BV, 2015)
This paper reports the normal consistency, setting time, workability and compressive strength results of Portland cement-fly ash-silica fume systems. The results show that water requirement for normal consistency was found to increase with increasing SF content while a decrease in initial setting time was found. Workability, measured in term of slump, was found to decrease with silica fume content (compared to blends without silica fume). However, it must be noted that despite the reduction in the slump values, the workability of Portland cement-fly ash-silica fume concrete in most cases remained higher than that of the Portland cement control concrete. Furthermore, the utilization of silica fume with fly ash was found to increase the compressive strength of concrete at early ages (pre 28 days) up to 145% with the highest strength obtained when silica fume was used at 10 wt%. Moreover, scanning electron micrographs show that utilization of fly ash with silica fume resulted in a much denser microstructure, thereby leading to an increase in compressive strength. © 2009 Elsevier Ltd. All rights reserved.